Analisis Yuridis Kerjasama Bisnis Menggunakan Jaminan Antara CV Mitra Sejati Abadi dengan Peternak Ayam Pedaging di Kabupaten Magelang - Rizaqitama Kalima Nugraha (UIN Sunan Kalijaga Yogyakarta, 2018)
The world of broiler farming business in CV. Mitra Sejati Abadi Wilayah Magelang uses collateral in business cooperation. Business cooperation built with a partnership system with farmers in the production process is a risk principle (loss / profit). The principle is applied with the aim if the loss is a shared responsibility and if profit is shared satisfaction. The point of balance of profit / loss depends on the national market price. This research data collection technique by conducting interviews with CV. Mitra Sejati Abadi in Magelang Region and 3 (three) partner farmers who have different guarantees, cases and sub-districts. The nature of this research is descriptive-analytical, namely research that aims to describe the practice of cooperation between CV Mitra Sejati Abadi and the farmers in the Magelang region. The research approach used is juridical empirical, which analyzes reality based on the Civil Code and data collected from CV. Mitra Sejati Abadi Magelang region and partner farmers in several sub-districts in the Magelang regency. This research shows that there are some errors in the agreement which will be discussed further.